Kant, the press, and the public use of reason - Donald, James (Javnost (Ljubljana), 2003)
Is it wise to structure critical discussion of the media around a normative ideal of publicness? This article suggests some potential problems by re-examining Kant's conception of the public use of reason, primarily as articulated in his newspaper article, "An Answer to the Question: What Is Enlightenment?" (1784). Kant's account of the enthusiasm of a German newspaper-reading public for the French Revolution not only introduces an aesthetic dimension into political judgment, but also prefigures the strategies of media critique. The limits of "the public" as an optic though which to judge the social functions of the media are discussed in the light of Kierkegaard's phenomenology and Ian Hunter's recent excavation of the tradition of civil philosophy associated with Pufendorf and Thomasius.
Keywords: Kant, Immanuel, 1724-1804; družbeno vedenje; javno mnenje; mass media; množični mediji; časniki; časopisi; razsvetljenstvo; Age of Enlightenment; svoboda; democracy; demokracija